2021
DOI: 10.3390/cancers13246153
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Tumor Cells Enumeration from the Portal Vein for Risk Stratification in Early Pancreatic Cancer Patients

Abstract: Background. Effective biomarkers are needed to enable personalized medicine for pancreatic cancer patients. This study analyzes the prognostic value, in early pancreatic cancer, of single circulating tumor cell (CTC) and CTC clusters from the central venous catheter (CVC) and portal blood (PV). Methods. In total, 7 mL of PV and CVC blood from 35 patients with early pancreatic cancer were analyzed. CTC were isolated using a positive immunomagnetic selection. The detection and identification of CTC were performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…Within the context of this result, AC is recommended after NAC and resection regardless of node and margin status. Other studies also have provided scientific evidence supporting the results presented in this study. The subgroup with higher pathological T category or higher tumor differentiation grade, which showed significant associations with lower mortality by AC, has been reported to have more circulating tumor cells …”
Section: Discussionsupporting
confidence: 90%
“…Within the context of this result, AC is recommended after NAC and resection regardless of node and margin status. Other studies also have provided scientific evidence supporting the results presented in this study. The subgroup with higher pathological T category or higher tumor differentiation grade, which showed significant associations with lower mortality by AC, has been reported to have more circulating tumor cells …”
Section: Discussionsupporting
confidence: 90%
“…In contrast, CTC released from tumors as pre-formed clusters, where CTC and myeloid cells are already aggregated together, may use GM-CSF to alter the function of the myeloid cells toward a more stromal-like role that promotes inflammation and prevents cytotoxic T cell-induced apoptosis in the portal microenvironment. Recent reports on CTC detection in multiple cancer types have suggested that the epithelial to mesenchymal transition phenotype of CTC may be indicative of further development of aggressive CTC subpopulations with high metastatic potential [ 9 , 42 47 ]. Using our FACS selection panels of CD44+CD147+EPCAM+/CK+CD45- for portal blood CTC in this and previous studies of PDAC CTC [ 7 , 11 ] we have collected both EPCAM+ and CK+ populations of CTC whenever possible but have routinely not examined the characteristics of EPCAM+CK- and EPCAM-CK+ subpopulations within the portal blood.…”
Section: Discussionmentioning
confidence: 99%
“…Addition of more selective markers as they are discovered could allow for better definition of the metastatic potential of individual CTC clones within the portal blood population. Interstitial biomarkers such as Twist and Vimentin have been found advantageous to detection of aggressive CTC in lung [ 45 , 47 ], breast [ 45 ], and recently, pancreatic cancers [ 42 46 ] in fluorescence immunohistochemical (IHC) staining and microscopy-based selection methods. Intracellular staining for vimentin has been suggested for distinguishing tumor cells from fibroblasts by IHC or flow cytometry.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of CTCs also did not differ between the two sampling sites in this study. A study by Padillo-Ruiz et al [ 38 ] also reported no differences between the portal and peripheral blood in terms of the detection rate (100% vs 100%) and number of CTCs (median 310 vs 405.7, P = 0.239). A comparison of the CTC detection rate and number between the portal vein and peripheral blood in patients with PC is summarized in Table 1 .…”
Section: Clinical Utility Of Portal Venous Ctcsmentioning
confidence: 93%